The Job Demands and Resources Related to COVID-19 in Predicting Emotional Exhaustion and Secondary Traumatic Stress Among Health Professionals in Spain - Moreno-Jiménez, Jennifer E.; Blanco-Donoso, Luis Manuel; Chico-Fernández, Mario; Belda Hofheinz, Sylvia; Moreno-Jiménez, Bernardo; Garrosa, Eva (Frontiers in Psychology, 2021)
The current COVID-19 crisis may have an impact on the health professionals’ mental health in the frontline, specifically in the increase of occupational psychosocial risks, such as emotional exhaustion and secondary traumatic stress (STS). Thus, we aim to explore the job demands and resources during the COVID-19 crisis in predicting emotional exhaustion and STS among health professionals. The present study is a descriptive and correlational cross-sectional design conducted in different hospitals and health centers of Spain. The sample consisted of 221 health professionals in the face of COVID-19. An online survey was created and nationwide distributed from 20th March to 15th April in which were assessed: sociodemographic and occupational data, fear of contagion, contact with death/suffering, lack of material and human protection resources (MHRP), challenge, emotional exhaustion, and STS. Descriptive findings show high levels of workload, contact with death/ suffering, lack of MHPR and challenge, and moderately high for fear of contagion, emotional exhaustion, and STS. We found an indirect significant effect of lack of MHPR on predicting (1) emotional exhaustion through the workload and (2) on STS through fear of contagion, contact with death/suffering, and workload. To conclude, this study examines the immediate consequences of the crisis on health professionals’ well-being in Spain, emphasizing the job demands related to COVID-19 that the health professionals are facing, and the resources available in the health contexts. The promising findings may boost the follow-up of this crisis among health professionals to prevent them from the long-term consequences.